Drug repurposing for Dravet syndrome in scn1Lab−/− mutant zebrafish. (20th January 2019) - Sourbron, Jo; Partoens, Michèle; Scheldeman, Chloë; Zhang, Yifan; Lagae, Lieven; de Witte, Peter
Summary: Dravet syndrome (DS) is a severe genetic epileptic encephalopathy with onset during the first year of life. Zebrafish models recapitulating human diseases are often used as drug discovery platforms, but also for drug repurposing testing. It was recently shown that pharmacological modulation of three serotonergic (5‐HT) receptors (5‐HT1D, 5‐HT2C, 5‐HT2A ) exerts antiseizure effects in a zebrafish scn1Lab −/− mutant model of DS. Using the zebrafish DS model, our aim was to examine the possibility of repurposing efavirenz (EFA), lisuride (LIS), and rizatriptan (RIZA), marketed medicines with a 5‐HT on‐ or off‐target profile, as antiepileptic drugs for DS. To examine whether these compounds have a broader antiseizure profile, they were tested in pentylenetetrazol and ethyl ketopentenoate (EKP) zebrafish models. Pharmacological effects were assessed by locomotor behavior, local field potential brain recordings, and bioluminescence. EFA was active in all models, whereas LIS was selectively active in the zebrafish DS model. Mainly, a poor response was observed to RIZA. Taken together, our preclinical results show that LIS could be a potential candidate for DS treatment. EFA was also active in the EKP model, characterized by a high level of treatment resistance, and hence these data are potentially important for future treatment of drug‐resistant epilepsy.